THE COMPARISON OF APPLICATION OF STOCK RETURN EVALUATION IN RECORDED COMPANIES IN LQ 45 FOR THE 2012-2016 PERIOD - Neneng Susanti; Deden Novan Setiawan Nugraha (JEES: Journal of Economic Empowerment Strategy, 2019)
The purpose of this study is not only to compare the Capital Asset Price Model, Arbitration PriceTheory, Three Factor Price Model, Three Factor Price Model, and Five Factor Price Model to studythe Capital Asset Price Model, Price Arbitration Price Theory, Three Factor Price Model, FourFactors Pricing Model and Five Factors Pricing Model for excess returns and for determining thebest asset pricing model in terms of the ability to explain estimates of excess returns. This researchincludes explanatory research (explanatory research), namely looking at the relationship betweenresearch variables and testing hypotheses that have been formulated previously. This study examinesthe effect of variables in the asset pricing model and compares the asset pricing models in explainingexcess returns. Based on the results of the research that has been carried out the best model that canbe used in assessing the asset pricing model is the five Price Model Factors, this is evidenced by thevalue of R2 or R Square of 89.4%, the value is greater than the value of R2 or R Square CapitalAsset Pricing Model, Arbitration Price Theory, Three Price Factor Models, and Four Price FactorModels, which were 34.7%, 55.2%, 77.2% and 79% respectively